2015
DOI: 10.1038/bmt.2015.69
|View full text |Cite|
|
Sign up to set email alerts
|

High-dose therapy and autologous hematopoietic cell transplantation as front-line consolidation in chronic lymphocytic leukemia: a systematic review

Abstract: High-dose therapy (HDT) followed by autologous hematopoietic cell transplantation (auto-HCT) is offered to patients with chronic lymphocytic leukemia (CLL) both as front-line consolidation and in the relapsed setting. The role of HDT in the front-line consolidation setting in CLL is uncertain. Literature search of PUBMED and Cochrane until 14 November 2014 and the last 2 years of abstracts from relevant conferences was undertaken. End points included benefits (overall survival; OS, PFS, event-free survival; EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Emergence of ibrutinib, a BCR inhibitor, and other targeted therapies that have proved to be effective treatment options for CLL even in high-risk disease has undoubtedly challenged the appropriateness of the 2007 EBMT consensus recommendations [19,20]. Several randomized controlled trials (RCT) and a meta-analysis have shown that high-dose chemotherapy and autologous HCT do not offer an overall survival (OS) advantage compared with conventional chemotherapy or chemoimmunotherapy; accordingly, relapsed CLL after an autologous HCT is not considered, today, as a prerequisite for an allo-HCT [21-25]. Moreover, autologous HCT has been abandoned from current treatment algorithms for CLL [21-25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergence of ibrutinib, a BCR inhibitor, and other targeted therapies that have proved to be effective treatment options for CLL even in high-risk disease has undoubtedly challenged the appropriateness of the 2007 EBMT consensus recommendations [19,20]. Several randomized controlled trials (RCT) and a meta-analysis have shown that high-dose chemotherapy and autologous HCT do not offer an overall survival (OS) advantage compared with conventional chemotherapy or chemoimmunotherapy; accordingly, relapsed CLL after an autologous HCT is not considered, today, as a prerequisite for an allo-HCT [21-25]. Moreover, autologous HCT has been abandoned from current treatment algorithms for CLL [21-25].…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials (RCT) and a meta-analysis have shown that high-dose chemotherapy and autologous HCT do not offer an overall survival (OS) advantage compared with conventional chemotherapy or chemoimmunotherapy; accordingly, relapsed CLL after an autologous HCT is not considered, today, as a prerequisite for an allo-HCT [21-25]. Moreover, autologous HCT has been abandoned from current treatment algorithms for CLL [21-25]. Recognizing the pressing need to incorporate the new realities of treating CLL in this modern treatment era [19], the American Society for Blood and Marrow Transplantation convened a group of experts to develop clinical practice recommendations related to the role of allo-HCT for CLL.…”
Section: Introductionmentioning
confidence: 99%
“…In CLL, allo-HCT induces durable remissions and an OS rate exceeding 50% at 3 years (with a plateau in survival curves), whereas auto-HCT has failed to demonstrate a survival advantage when compared with chemotherapy or chemoimmunotherapy as a consolidative strategy [29][30][31][32][33]. In our opinion, this represents an advantage for allo-HCT over auto-HCT in RS, especially when considering that 35% of cases who receive an auto-HCT for RS relapsed with CLL [35].…”
Section: Article In Pressmentioning
confidence: 59%
“…One particular challenge is the presence of residual CLL disease in RS cases. Several randomized controlled trials and a meta-analysis comparing HDT/ auto-HCT versus conventional chemotherapy (or chemoimmunotherapy) in patients with CLL failed to show an OS benefit for HDT/auto-HCT in CLL [29][30][31][32][33]. On the other hand, offering an allo-HCT to patients with RS (with residual CLL) might prove to be a more beneficial strategy aimed at eradicating both diseases, but certainly at the expense of higher nonrelapse mortality (NRM).…”
Section: Hematopoietic Cell Transplantationmentioning
confidence: 94%